Quality in public library services: Are we talking about the same thing? - Lozano, Roser (Anuario ThinkEPI, 2008)
The report "Our libraries: where has all the cash gone?" by Tim Coates , which describes the situation of the public libraries in London, is the starting point for reflections about the quality of public library services and about the need to link them with the needs and expectations of citizens, who are the beginning and the end of the road for public libraries, and then to undertake the expedition together.
Keywords: Public libraries; Public Library Policy; Quality; Management.